Thyroid functions and serum lipid profile in metabolic syndrome - Gutch, Manish (Biomed J, 2017)
BACKGROUND: Thyroid hormones are known to affect energy metabolism. Many patients of metabolic syndrome have subclinical or clinical hypothyroidism and vice versa. To study the correlation of thyroid profile and serum lipid profile with metabolic syndrome. METHOD: It is a hospital based cross sectional case-control study carried out in tertiary care health center, we studied thyroid functions test and serum lipid profile in 100 metabolic syndrome patients according to IDF criteria and a similar number of age, gender and ethnicity matched healthy controls. RESULT: We found that serum HDL was significantly lower (p < 0.001) in cases (41.28 ± 8.81) as compared to controls (54.00 ± 6.31). It was also found that serum LDL, VLDL, triglyceride levels and total cholesterol were found to be significantly higher (p < 0.001) in cases than controls. Serum TSH levels of subjects in cases group (3.33 ± 0.78) were significantly higher (p < 0.001) than that of controls (2.30 ± 0.91) and significantly lower levels of T(4) (p < 0.001) in the patients of metabolic syndrome (117.45) than in controls (134.64) while higher levels of T(3), although statistically insignificant in the patients of metabolic syndrome. CONCLUSION: Thyroid hormones up-regulate metabolic pathways relevant to resting energy expenditure, hence, obesity and thyroid functions are often correlated.